An Analysis Of Marriage Guardianship Provisions In Somalia And Indonesia: A Comparative Study Of Somalia Family Law And Indonesian Islamic Law - Azmi, Lalu Miptahul; Ghazali, Muhammad Said; Prihartini, Arina Amalia; Ghazali, Ahmad Alimuddin (Syntax Literate, 2024)
Indonesia and Somalia are both categorized as nations with a predominant Muslim population following to the Shafi'i Madhab (school of thought). However, despite this similarity, there are notable distinctions in the Islamic family law rules and their enforcement between the two countries. An important distinction is in the divergence of marriage guardianship regulations between Indonesia and Somalia. In Indonesia, marriage guardians are mandatory and considered an essential component of the marriage process, whereas in Somalia, the opposite is genuine. In Somalia, a marriage guardian is not mandatory for marriage. This comparative phenomenon is quite distinctive and warrants further in-depth study. Despite both countries are followers of the Shafi'i school of thought in Islam, their respective applications of Islamic Family Law differ significantly. This study employs the library research method, specifically utilizing a Normative Juridical approach. Ultimately, the variations in marriage guardian legislation between these two nations can be attributed to socio-historical disparities and devotion to different schools of belief by their respective populations. In Indonesia, guardianship law follows the Syafii school of thought, which is in line with the beliefs of the majority of the population. Conversely, Somalia's law is based on the Hanafi school of thought, which emphasizes gender equality and justice in all legislation.